2013
DOI: 10.1115/1.4025138
|View full text |Cite
|
Sign up to set email alerts
|

Different Fatigue Dynamics Under Statistically and Spectrally Similar Deterministic and Stochastic Excitations

Abstract: Estimating and tracking crack growth dynamics is essential for fatigue failure prediction. A new experimental system-coupling structural and crack growth dynamics-was used to show fatigue damage accumulation is different under chaotic (i.e., deterministic) and stochastic (i.e., random) loading, even when both excitations possess the same spectral and statistical signatures. Furthermore, the conventional rain-flow counting method considerably overestimates damage in case of chaotic forcing. Important nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…From this phase space representation, a feature vector is identified which characterizes the fast-time dynamics. For example, each snapshot can be characterized by a particular nonlinear metric, such as characteristic distance (Nguyen et al, 2014), which captures the geometrical features of the attractor and is fast and easy to estimate. This process is repeated for many snap-shots as damage accumulates in the system.…”
Section: Phase Space Warpingmentioning
confidence: 99%
“…From this phase space representation, a feature vector is identified which characterizes the fast-time dynamics. For example, each snapshot can be characterized by a particular nonlinear metric, such as characteristic distance (Nguyen et al, 2014), which captures the geometrical features of the attractor and is fast and easy to estimate. This process is repeated for many snap-shots as damage accumulates in the system.…”
Section: Phase Space Warpingmentioning
confidence: 99%
“…4 Damage Growth Rate Law In Ref [18], we have showed that standard linear damage Palmgren-Miner law and Rainflow-counting method failed to estimate damage during fatigue testing under chaotic loading, while being adequate for random loading, which had the same statistical and spectral properties as chaotic. For deterministic loads, these experiments indicated that fatigue life depends not only on the number of stress cycles but also on the divergence rate λ, which measures the average rate of the expansion and folding process in an attractor.…”
Section: The Effective Stiffnessmentioning
confidence: 99%
“…The fatigue experiments described in Ref. [18] are used to validate the new fatigue model under irregular, non-cyclic loadings. The details of the experimental system are given in Refs.…”
Section: Experimental Validationmentioning
confidence: 99%
See 2 more Smart Citations